17 KOR SISPA UMPSA students receive certificate of Civil Defense Junior Lieutenant - Nor Salwana, Mohammad Idris (UMPSA, 2024)
PAGOH, 18 August 2024 – A total of 17 Civil Defense Student Corps (SISPA) students from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) received their credentials as Civil Defense Junior Lieutenants during the Civil Defense Student Corps End of Training Parade (KOR SISPA) National Level 15th Year 2024 at Padang Kawad, Universiti Tun Hussein Onn Malaysia (UTHM).